МАКТАБГАЧА ТАЪЛИМ: КЕЛАЖАК ИСЛОҲОТИ - Календарова, З. (SCIENCE and SOCIETY, 2018)
The article deals with the problems in the system of pre-school education, ways of their liquidation and improvement of this system pointed in government’s laws.